Intertidal intercepted sediment at jetties along the Gulf of Thailand - Saengsupavanich, Cherdvong; Yun, Lee Shin; Lee, Lee Hin; Sanitwong-Na-Ayutthaya, Sarinya (Frontiers in Marine Science, 2022)
Sand bypassing is one of the promising solutions to rectify jetty-induced coastal erosion. Estimating alongshore sediment transport rate and understanding hydrodynamic conditions at a jetty are crucial for successful downdrift erosion management. This research investigated three major jetties in Thailand (Cha Am jetty, Krai jetty, and Na Saton jetty) that protrude across the surf zone and completely intercept alongshore sediment transport. Sub-aerial and inter-tidal field surveys by Real Time Kinematic (RTK) technique were undertaken in 2019 and 2020. The collected data was processed and overlaid to calculate the amount of sediment deposition at the updrift jetty. Numerical simulations using MIKE21 SW and MIKE21 HD were carried out in order to understand how waves and water currents interacted with the jetties. From the results, we found that the Cha Am jetty trapped approximately 38,187 cu.m/yr of the alongshore sediment. While the Krai jetty intercepted approximately 34,170 cu.m/yr of the alongshore drift, and approximately 65,951 cu.m/yr of longshore sediment transport was blocked by the Na Saton jetty. Such estimated amounts of deposited sediment are the quantities that should be bypassed at each jetty. Budgets and implementation plans for sand bypassing can be prepared. Decision makers can decide how to manage updrift deposition and downdrift erosion.